Chloride Fertilizers Increase Spring Wheat Yields in the Northern Great Plains. (1st January 2017) - Graham, Christopher; Woodard, Howard; Bly, Anthony; Fixen, Paul; Gelderman, Ronald
Abstract : Core Ideas: Across all site‐years of the study, results show a statistically significant grain yield increase of 0.17 t ha −1 . Where pre‐plant soil test Cl − levels were lower than 1.87 mg kg −1, fertilizer Cl − applications increased grain yield by 0.26 t ha −1 with an average return of 18.42 ha −1 . The potential profitability of Cl − fertilizer application is highly dependent on the choice of cultivar. Chloride (Cl − ) plays an important role in osmoregulatory functions within the plant and aids in disease suppression. Previous research established a soil sufficiency level and fertilizer Cl − recommendations based on a 0‐ to 60‐cm soil depth sample. This work found spring wheat ( Triticum aestivum L.) yield was responsive to Cl − fertilizers on soils with low Cl − soil tests. However, the response was often variable and cultivar specific, which suggested that further refinements to the Cl − fertilizer recommendations were necessary. In this research, the impact of Cl − fertilizer on yield, test weight, and protein of three spring wheat cultivars (Forge, Marshall, and Oxen ) was tested in a randomized complete block experiment in 1997, 1998, 1999, 2000, and 2002 in Aurora, SD. Across all years and cultivars, results showed a statistically significant grain yield increase of 0.17 t ha −1 with Cl − addition. Similarly, Cl − increased test weight by 0.98 kg hL −1 . Protein, on the other hand, showed a cultivar by Cl − response with Cl − increasing protein by 2.28 g protein kg −1 in Oxen and decreasing protein 2.52 g protein kg −1 in Forge. Where pre‐plant‐soil test Cl − levels were lower than 1.87 mg kg −1, fertilizer Cl − applications increased grain yield by 0.26 t ha −1 with an average return of 18.42 ha −1 . However the potential profitability of Cl − fertilizer application is highly dependent on the choice of cultivar. Further research is necessary to assess if increasing spring rainfall in the region will increase Cl − yield responses.